Synergi Membuat Pupuk Organik dari Limbah Air Cucian Beras untuk Pupuk Tanaman - Sapariyah, Rina Ani; Susanti, Nani Irma; Saryanti, Endang (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
During the Covid-19 pandemic, the order of people's lives has changed dramatically. The strict application of the 5M rule makes the space limited. To be able to survive healthily and happily, activities are needed that can provide positive energy as well as be useful for sustainability in meeting life's needs. One of the trends is planting both ornamental and vegetable plants and even medicinal plants or kitchen spices in the yard. For the plants to thrive, the fertilizer used uses the rice washing water waste that is produced every day. So far, housewives will flush rice washing water waste directly on the plants. The community service team provides socialization, training, and assistance in making liquid organic fertilizer that can be made by housewives in their respective homes. The synergy between household members in making Liquid Organic Fertilizer from rice washing water waste, so that it is more efficient and effective